(untitled) (Revista Ciência Agronômica, 2023)
Greater ruminal degradability has been reported in mutant plants with brown midrib (bmr). The aim of this study was to evaluate the in situ degradability of dry matter (DM), neutral detergent fibre (NDF) and crude protein (CP) in the experimental sorghum-sudangrass bmr hybrids BR007 x Tx2784bmr and Tx635x Tx2785bmr, conventional experimental hybrids CMSxS206 x Tx2784 and Tx636 x Tx2785, and the control hybrid BRS801, harvested 51 days after planting. Three sheep with ruminal cannulae were used. The experimental design was of randomised complete blocks in subdivided lots. The mean values for DM and NDF disappearance were higher in the bmr hybrids after 6 h incubation. These plants had a higher rate of degradation (mean value of 6.93%/h) for fraction b of the DM compared to conventional plants (mean value of 5.73%/h), and greater effective DM degradability. The mean values for effective NDF degradability at passage rates of 2, 5 and 8%/h were 72.7% and 62.0%, 56.1% and 45.6%, and 47.1% and 37.3% for the bmr and conventional hybrids respectively. The experimental mutant hybrids showed higher values for effective CP degradability in relation to the remainder, however, the differences were more subtle in relation to those seen for DM and NDF. The results of the present work show the potential of using sorghum-sudangrass bmr hybrids in systems of ruminant production with high nutritional requirements.